STRATEGI KOMUNIKASI EFEKTIF DALAM MEMBANGUN DAN MEMELIHARA HUBUNGAN DENGAN KLIEN (STUDI PADA PT HASTA AYU NUSANTARA) - Rini Kustini Amalia (Jurnal Komunikasi, 2026)
Communication plays an important role in supporting the success of service companies, particularly in building and maintaining relationships with clients. Effective relationships between companies and clients can create trust, increase satisfaction, and ensure the sustainability of cooperation. PT Hasta Ayu Nusantara, as a company providing professional workforce services, requires appropriate communication strategies to meet client needs and minimize misunderstandings in the cooperation process. This study aims to identify the communication strategies implemented by PT Hasta Ayu Nusantara in building and maintaining relationships with clients, the forms of communication used, as well as the factors that support and hinder communication effectiveness. This research employs a qualitative approach using a case study method. Data collection techniques include in-depth interviews, observation, and documentation. The results show that PT Hasta Ayu Nusantara implements planned communication strategies through interpersonal communication, two-way communication, and the use of digital and face-to-face communication media. These communication strategies have proven effective in strengthening professional relationships, increasing client trust, and maintaining the continuity of company cooperation.